THE FREEDOM OF WOMAN IN THE EARLY 20TH CENTURY ENGLISH NOVEL: A CASE ON VIRGINIA WOOLFâ€™S NOVEL TO THE LIGHTHOUSE - Nurrachman, Dian (Saksama: Jurnal Sastra, 2023)
Freedom is always a longing for everyone. Freedom is a dream that must be achieved in broadly life; it is not only a kind of utopia, but should be united in reality. By the freedom one can do anything, for the freedom is over all. Once the freedom being shackled, the struggle for liberation will become a necessary one. Such a struggle is not always and only appeared in the physical appearances, but also appears in the ideas against the establishment of hegemony. Those thesis statements above are discursive formations that is used to analyze the struggling ideas of Lily Briscoe; one of the characters that in Virginia Woolfâ€™s novel To the Lighthouse. Lily Briscoe is important to appear because she broaches ideas, statements, and questions that refer to her struggle for liberating herself from the patriarchal hegemony, including patriarchal ideal of womanhood. In accordance with such a struggle, the combination theoretical framework of Marxist-Feminism with a little â€œdeconstructiveâ€ reading will be an interesting discussion here.